1987
DOI: 10.1007/bf00274715
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the anther-culture response of three spring wheat crosses

Abstract: Anther-culture response was examined among three spring wheat (Triticum aestivum L.) cultivars to evaluate the genetic component of response and to determine whether androgenetic performance could be improved by selection. The three lines, the three possible F1's among the three lines, their F2's, and the backcrosses to the parents were evaluated for callus production and regeneration capacity. Significant variation was observed among the generations of the three crosses for callus formation. Genetic variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…In order to reduce the random variation which appears to be a large component of the quantitative variation observed (Deaton et al 1987), we recommend taking the following precautions:…”
Section: Importance Of the Spike Effectmentioning
confidence: 99%
“…In order to reduce the random variation which appears to be a large component of the quantitative variation observed (Deaton et al 1987), we recommend taking the following precautions:…”
Section: Importance Of the Spike Effectmentioning
confidence: 99%
“…Their estimates were 0.82, 0.82 and 0.72, respectively. Deaton et al (1987) reported that there was considerable variation among the three spring wheat crosses for the heritability estimates. They suggested that a large component of the quantitative variation was due to random variation.…”
Section: Partitioning Of Genetic Variancementioning
confidence: 99%
“…A predominantly additive gene action exists for microsporederived embryo induction (Charmet & Bernard, 1984 ;Miah et al ., 1985 ;Deaton et al ., 1987 ;Wu & Chen, 1987 ;Powell, 1988 ;Agache et al ., 1988 ;Quimio & Zapata, 1990 ;Koba et al ., 1993) and green plant regeneration (Tuvesson et al ., 1989 ;Zhou & Konzak, 1992 ;Shimada et al ., 1993) . Estimated heritabilities were high for anther culture ability (Charmet & Bernard, 1984 ;Lazar et al ., 1984b ;Miah et al ., 1985) .…”
Section: Influence Of the Nuclear Genomementioning
confidence: 99%